Implementasi Metode Islamic Montessori dalam Menanamkan Nilai-Nilai Pendidikan Islam di Sekolah Kiswah Tangerang Selatan - Annisa Kirana Putri; Pahrurroji Pahrurroji; Sri Widyastri (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Education in schools is often perceived as a process that limits individual freedom. Therefore, the educational process is considered incapable of changing the individual. Instead, education tends to be a tool to maintain existing social structures and tends to meet only the needs of industry. This study aims to analyze the process of implementing the Islamic Montessori method in instilling the values of Islamic education in the South Tangerang Kiswah School, as well as explaining the supporting and inhibiting factors in implementing the Islamic Montessori method in instilling the values of Islamic education in the South Tangerang Kiswah School. This study uses a type of qualitative research, with a qualitative descriptive approach. The results of this study indicate that: 1)The implementation of the Islamic Montessori method in instilling the values of Islamic education is carried out by instilling the values of faith, worship and morals that are adapted to the learning areas in the Islamic Montessori method. 2) Factors that influence the inculcation of Islamic educational values through the Islamic Montessori method in Kiswah Schools, namely: supporting factors (teachers as educators and facilitators, school environment, parents, and friends), and inhibiting factors (self and environment family).